Optimalisasi Program Simpanan Berhadiah Dalam Upaya Meningkatkan DPK Pada BSI KCP Rembang Sudirman - Maulida, Lutfiana; Qoes Atieq, Muhammad (Jurnal Ilmiah Ekonomi Islam, 2024)
Based on data from BSI's annual report, BSI's total deposits from 2021 continue to increase. However, BSI still faces challenges in increasing its deposits to strengthen its liquidity.. The purpose of this research is to find out how the strategy of optimizing the prize savings program and its impact on increasing DPK. The method used is qualitative method. The population used is BSI employees, while the sample used is BSI employees and taken using purposive sampling technique. The data source used is primary data from informants through interviews. The results showed that efforts to optimize the prize savings program at BSI KCP Rembang Sudirman were carried out by segmentation, promotion, and continuous offering, and visiting customers' homes for offers. The results of this optimization have had a positive effect on the increase in DPK since the beginning of 2024 so that the BSI KCP Rembang Sudirman rating is quite good because of consistent daily achievements. In addition to increasing DPK, optimizing this program can increase the number of new customers because it provides benefits to customers. The recommendation of this research is that Bank Syariah Indonesia must increase innovation through programs that can provide more value or benefits to customers.